Retrospective analysis of COVID-19 clinical and laboratory data: Constructing a multivariable model across different comorbidities - Mahdieh Shokrollahi Barough; Mohammad Darzi; Masoud Yunesian; Danesh Amini Panah; Yekta Ghane; Sam Mottahedan; Sohrab Sakinehpour; Tahereh Kowsarirad; Zahra Hosseini-Farjam; Mohammad Reza Amirzargar; Samaneh Dehghani; Fahimeh Shahriyary; et al. (Elsevier, 2024)
Background: The clinical pathogenesis of COVID-19 necessitates a comprehensive and homogeneous study to understand the disease mechanisms. Identifying clinical symptoms and laboratory parameters as key predictors can guide prognosis and inform effective treatment strategies. This study analyzed comorbidities and laboratory metrics to predict COVID-19 mortality using a homogeneous model. Method: A retrospective cohort study was conducted on 7500 COVID-19 patients admitted to Rasoul Akram Hospital between 2022 and 2022. Clinical and laboratory data, along with comorbidity information, were collected and analyzed using advanced coding, data alignment, and regression analyses. Machine learning algorithms were employed to identify relevant features and calculate predictive probability scores. Results: The frequency and mortality rates of COVID-19 among males (19.3 %) were higher than those among females (17 %) (p = 0.01, OR = 0.85, 95 % CI = 0.76-0.96). Cancer (p < 0.05, OR = 1.9, 95 % CI = 1.48-2.4) and Alzheimer's (p < 0.05, OR = 2.36, 95 % CI = 1.89-2.9) were the two most common comorbidities associated with long-term hospitalization (LTH). Kidney disease (KD) was identified as the most lethal comorbidity (45 % of KD patients) (OR = 5.6, 95 % CI = 5.05-6.04, p < 0.001). Age > 55 was the most predictive parameter for mortality (p < 0.001, OR = 6.5, 95 % CI = 1.03-1.04), and the CT scan score showed no predictive value for death (p > 0.05). WBC, Cr, CRP, ALP, and VBG-HCO3 were the most significant critical data associated with death prediction across all comorbidities (p < 0.05). Conclusion: COVID-19 is particularly lethal for elderly adults; thus, age plays a crucial role in disease prognosis. Regarding death prediction, various comorbidities rank differently, with KD having a significant impact on mortality outcomes.